Идеал, справедливость, счастье - Дубко Елена Леонидовна (Издательство МГУ, 1989)
Экземпляры: КХ (20110217) / Инвентарный номер: 938309 / Цена: 0.70 / Сис.шифр: 87.713 / Авт.знак: Д 79 / ГРНТИ: 02 / ББК: 87.702